2016
DOI: 10.3892/br.2016.734
|View full text |Cite
|
Sign up to set email alerts
|

Study on lumbosacral nerve root compression using DTI

Abstract: Abstract. Diffusion tensor imaging (DTI) can objectively describe the distribution of nerve roots in morphology, and provide a set of objective reference data on the quantitative indicators. The present study aimed to investigate the value of DTI in lumbosacral nerve root compression in patients with lumbar intervertebral disc degeneration. DTI was performed in 45 patients with lumbar intervertebral disc degeneration. Apparent diffusion coefficient (ADC) and fractional anisotropy (FA) values were measured in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As the DTI technique has evolved, the movement of water molecules can be accurately measured using DTI parameters such as the FA and ADC values. These values have been found to be capable of analysing the nerve root condition in greater detail than conventional MRI10111214.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the DTI technique has evolved, the movement of water molecules can be accurately measured using DTI parameters such as the FA and ADC values. These values have been found to be capable of analysing the nerve root condition in greater detail than conventional MRI10111214.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known as diffusion anisotropy, and selectively recording this information is referred to as diffusion tensor imaging (DTI). DTI is the only method that can give an indirect view of the microstructure of nervous tissue in addition to the pathway of the fibres 10 11 12 13 . The diffusion data can help determine the quantitative diffusion values, such as the ADC and fractional anisotropy (FA) values that reflect the directionality of the molecular diffusion.…”
mentioning
confidence: 99%
“…A total of 683 subjects were studied across 24 DTI articles. 177 patients with lumbar spinal canal stenosis (LSCS) in 5 articles 11,12,16,17,20) , 143 patients with lumbar disc herniation (LDH) in 7 articles 7,13,15,20,21,23,29) , 112 patients with lumbar radiculopathy in 3 articles 10,19,22) , 36 patients with foraminal stenosis (FS) in 6 articles 9,11,16,20,27,28) , 2 patients with lower back pain in one article 20) , 3 cases with diastematomyelia and one case with tethered cord in one article 30) , and one case with spina bifida in one article 26) were included. 7 post mortem subjects were investigated in one article 8) .…”
Section: Diffusion-weighted Mr Neurographymentioning
confidence: 99%
“…All 17 articles 7,[9][10][11][12][13][15][16][17]19,20,22,23,[27][28][29][30] . Except for one continued.…”
Section: Measurement Of Dti Parametersmentioning
confidence: 99%
“…1 Several studies that used EPI-DTI recently showed that tractography can visualize the lumbar nerves, and the degree of lumbar nerve damage was quantitatively evaluated using fractional anisotropy (FA) by identifying the preferential water molecule diffusion. 2 These previous studies on EPI-DTI indicated that the FA values decreased in the presence of peripheral nerve compression with nerve damage because of neurodegeneration, such as interstitial space widening, Wallerian degeneration, and axonal demyelination, which induces increased perpendicular diffusion vector compared with the normal nerves. 3 Although EPI-DTI has great potential for the evaluation of lumbar nerve compression, several problems, such as long acquisition times in obtaining a sufficient signal-to-noise ratio (SNR) using multiple signal averages, geometric distortion, and artifact susceptibility due to its high sensitivity to magnetic susceptibility, were observed.…”
Section: Introductionmentioning
confidence: 91%